Anti-Inflammatory Activity and Quality Control of Erysimum cheiri (L.) Crantz. (9th June 2021) - Mosleh, Ghazaleh; Azadi, Amir; Khademian, Sedigheh; Heidari, Reza; Mohagheghzadeh, Abdolali
Abstract : Wallflower ( Erysimum cheiri ) is employed as a popular herbal drug in traditional Persian medicine. Topical formulations including cerates, lotions, sitz baths, and poultices for inflammatory disorders such as arthritis, anal fissure, endometriosis, and mastitis are known. However, there is no monograph in current pharmacopoeia for the wallflower drug. The present study is aimed to screen in vitro anti-inflammatory activity of wallflower and perform quality control and characterization tests for different organs of the herb. In this regard, albumin denaturation activity, macroscopic and microscopic, phytochemical, HPTLC, and FT-IR characteristics were investigated. Wallflower showed strong anti-inflammatory activity compared to diclofenac sodium. The root (1.25, 2.5, and 5 mg/mL) and flower (10 mg/mL) extract exhibited higher anti-inflammatory activities than that of other plant organs at the same concentrations. Moreover, total ash was found higher in aerial parts (21.52 ± 0.06 % ) than flower (11.01 ± 0.03 % ), root (5.03 ± 0.03 % ), and seed (6.95 ± 0.06 % ), while water-soluble ash was higher in seed (34.89 ± 0.26 % ) than flower (5.00 ± 0.03 % ), aerial parts (7.16 ± 0.06 % ), and root (5.04 ± 0.01 % ). Acid-insoluble ash and sulphated ash were higher in root (9.50 ± 0.04 % ) and aerial part (28.37 ± 0.57 % ), respectively. In addition, loss on drying was ranged from 2.20 ± 0.20 % in flowers to 6.00 ± 0.10 % in aerial parts. On the other hand, HPTLC analysis verified cardenolide compounds in all organs of the herb, and quercetin was detected in the flavonoid fingerprint of acid hydrolysed flowers. According to FT-IR results, the observed spectral region at ~3500 cm -1 attributed to -OH stretching vibration. Also, C–H (~2900-2950 cm -1 ), isothiocyanate (~2340 cm -1 ), -C=O (~1740 cm -1 ), conjugated C=C of the aromatic ring (~1650 cm -1 ), and structure of the aromatic group (~1200-1000 cm -1 ) were monitored. This work is the first study to the best of our knowledge, suggesting wallflower as a potential drug candidate with the basis for a monograph in addition to initial in vitro anti-inflammatory data.